LITURGI YANG BERGERAK: KOREOGRAFI ROHANI DALAM IBADAH PUJIAN ALA DAUD - Kilat Kasanang (STT Bethel Indonesia Jakarta, 2025)
This study examines the profound role of bodily movement and choreography in Christian worship, advocating for its reintegration as an essential liturgical dimension, inspired by the Davidic model. It introduces